When should foetal pH measurements be performed after a prolonged deceleration? An experimental study in a fetal sheep model. (July 2018) - Dupuis, H.; Ghesquière, L.; De jonckheere, Julien; Aubry, E.; Sharma, D.; Deruelle, P.; Storme, L.; Houfflin-Debarge, V.; Garabedian, C.
Abstract: Objective: The aim of fetal heart rate monitoring during labour is to identify and prevent foetal distress, but its evaluation is not perfect. Fetal scalp blood sampling for pH measurement is one of the second-line methods of monitoring when fetal heart rate is classified as suspicious. This study aims to determine when pH testing should be performed after a prolonged deceleration. Study design: This was an experimental study in a fetal sheep model. A partial umbilical cord occlusion was performed for seven minutes followed by a recuperation period of 30 min. Hemodynamic parameters (heart rate, mean blood pressure and intra-amniotic pressure) and blood gases were recorded before occlusion (T0), during occlusion (T4), just after the end of occlusion (T7), and then 10, 20 and 30 min after occlusion (T17, T27 and T37 respectively). Results: Ten experiments were carried out. During partial cord occlusion, the fetal pH decreased significantly to acidosis. After a prolonged deceleration with fetal acidosis, the pH recovered to a normal value, defined by a pH greater than or equal to 7.25, after 20 min of recuperation. Conclusion: After a prolonged deceleration, fetal pH normalizes between 20 and 30 min thereafter. Thus, if a foetal blood sample is indicated, this delay must be respected in order to avoid inducing an unnecessary intervention decision.